Impact of coastal development on mangrove cover in Kilim river, Langkawi Island, Malaysia - Saad, Shahbudin; Ahmad, Zuhairi; Yunus, Kamaruzzaman (Northeast Forestry University, co-published with Springer, 2012)
We examined the impact of various coastal developments on mangrove cover along the Kilim River, Langkawi Island, Malaysia between 1996 and 2008. We analysed images from Systeme Probatoire d’Observation de la Tarre (SPOT) of Kilim River using supervised classification and Principal Component Analysis (PCA). Over 8% (176.83 ha) of mangrove cover was degraded along the Kilim River from its total area of 2153.07 ha during the past 14 years. We identified several causes of mangrove degradation, including mangrove clearing (38%), mangrove conversion to commercial area (21%), residential area (19%), agriculture (12%), aquaculture (12%) and wake current (6%). Langkawi is one of the main tourism islands in Malaysia. Tthe pace of coastal development throughout the entire island including Kilim River had suppressed the mangroves propagation over the years. Long term monitoring of mangrove ecosystems is essentials to ensure the survival and sustainability of mangrove associated biodiversity.